2012
DOI: 10.1002/ejoc.201200985
|View full text |Cite
|
Sign up to set email alerts
|

Atropisomeric Chiral Probes to Study the Supramolecular Organization in Porphyrin Self‐Assemblies

Abstract: A noncatalysed nucleophilic aromatic substitution was used to prepare the (bacterio)chlorophyll mimics 2‐Zn, 3‐Zn, 4‐Zn and 5‐Zn. The localisation of the two recognition groups on the same side of the porphyrin macrocycles in 2‐Zn, 4‐Zn and 5‐Zn produces, through metal–ligand interactions, oligomers that display both H‐ and J‐type aggregates. These supramolecular architectures were confirmed by the introduction of optically pure atropisomers in 5‐Zn, which produces chiral aggregates. The UV/Vis and electronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Although a few S N Ar reactions involving meso ‐nitrooctaethylporphyrin were reported decades ago, until recently they were not energetically investigated as methods for the meso ‐functionalization of porphyrins. Balaban and coworkers recently revealed that meso ‐bromodiarylporphyrins, which are readily obtained by the reactions of diarylporphyrins, also undergo S N Ar reactions in the presence of excess alkylamines to afford meso ‐( N ‐alkylamino)porphyrins in good yields ,,. Our group also reported the syntheses of meso ‐azidoporphyrins and meso ‐aminoporphyrins through S N Ar reactions ,.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Although a few S N Ar reactions involving meso ‐nitrooctaethylporphyrin were reported decades ago, until recently they were not energetically investigated as methods for the meso ‐functionalization of porphyrins. Balaban and coworkers recently revealed that meso ‐bromodiarylporphyrins, which are readily obtained by the reactions of diarylporphyrins, also undergo S N Ar reactions in the presence of excess alkylamines to afford meso ‐( N ‐alkylamino)porphyrins in good yields ,,. Our group also reported the syntheses of meso ‐azidoporphyrins and meso ‐aminoporphyrins through S N Ar reactions ,.…”
Section: Introductionmentioning
confidence: 81%
“…These functionalized porphyrins have been used as promising photosensitizers in dye‐sensitized solar cells . In addition, peripheral substituents play important roles during the construction of porphyrin‐based molecular materials through further substituent transformations or coordination‐driven self‐assembly . For these purposes, a considerable number of synthetic methods for the introduction of a variety of substituents have been developed over several decades.…”
Section: Introductionmentioning
confidence: 99%
“…More complicated supramolecular self-assembly behavior was observed for the enantiopure porphyrin, 108 (Figure 29) [88]. Whilst the monomeric species was essentially CD silent, the corresponding self-coordinated complex exhibited a noticeable CD signal in the region of Soret absorption consisting of three Cotton effects as a result of the interporphyrin exciton coupling.…”
Section: Chiral Porphyrinoidsmentioning
confidence: 92%
“…The interaction of porphyrins with O-, S-and N-nucleophiles allowed preparation of the corresponding substituted derivatives with high yields. [20][21][22] Despite the wide potential of experimental implementations the nucleophilic reactions remain virtually unstudied from the mechanistic point. The polarizability of the porphyrin polyaromatic system is the key factor for the versatility of these substrates.…”
Section: Introductionmentioning
confidence: 99%